Pengaruh Aromaterapi Ylang-Ylang terhadap Insomnia Ibu Hamil Trimester III di UPTD. Puskesmas Kuta II - Sugiari, Ni Luh (STIKES ADVAITA MEDIKA TABANAN, 2024)
Intoduction: Pregnancy is a sensitive phase in women's lives. Pregnant women have insomnia due to hormonal changes caused by adapting to the fetus's growth and development in the womb. To reduce the incidence of insomnia in pregnant women, non-pharmacological therapy is used, specifically ylang-ylang aromatherapy. The purpose of this study is to assess the impact of ylang-ylang aromatherapy on insomnia in third-trimester pregnant women. Metohds: This study used a quasi-experimental research methodology with a Non-Equivalent Control Group design and accidental sampling, with 34 pregnant women separated into two groups: the experimental group and the control group. The level of insomnia was measured using the PSQI questionnaire, then data analysis was carried out using Mann Whitney. Result: The results showed that there was a difference in the level of insomnia of TM III pregnant women in the experimental group after being given the intervention where the p-value was 0.00 < 0.05. Meanwhile, in the control group, the post-test p-value was 1,000 > 0.05, which means that there was no difference in the level of insomnia in the control group. Analysis using Mann Whitney found that there was a significant effect of giving ylang-ylang aromatherapy on insomnia in TM III pregnant women where the p-value was 0.00 < 0.05. Suggestion: From It is hoped that ylang-ylang aromatherapy will be employed as part of comprehensive midwifery care for TM III pregnant women to lower the occurrence of insomnia.